High-molecular polymer as well as preparation method and application thereof

By copolymerizing N-vinylpyrrolidone and polyoxyethylene ether monomers with acrylamide monomers, a high-molecular polymer with a comb-shaped branched structure was prepared, which solved the problems of insufficient conductivity and mechanical properties of polyoxyethylene ether solid electrolytes and achieved a high-efficiency improvement in battery performance.

CN120904402APending Publication Date: 2025-11-07SHANGHAI YUKING WATER SOLUBLE MATERIAL TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511083709.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-04
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Polyoxyethylene ether solid electrolytes have low room temperature conductivity, poor interfacial contact with certain electrodes, and insufficient mechanical properties, which limits their application in high-performance batteries.

Method used

A comb-shaped branched polymer was prepared by copolymerizing N-vinylpyrrolidone, polyoxyethylene ether monomers and acrylamide monomers to improve the ionic conductivity and mechanical strength of solid electrolytes and optimize electrode interface contact.

Benefits of technology

It improves the room temperature ionic conductivity of the solid electrolyte, enhances the cycle stability and electrochemical stability of the battery, and improves the charge and discharge speed and overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005531767590000021
    Figure BDA0005531767590000021
  • Figure BDA0005531767590000071
    Figure BDA0005531767590000071
  • Figure BDA0005531767590000081
    Figure BDA0005531767590000081
Patent Text Reader

Abstract

The invention relates to a high-molecular polymer as well as a preparation method and application thereof. The high-molecular polymer is prepared from the following raw materials in parts by weight: 20 to 35 parts of N-vinyl pyrrolidone, 20 to 40 parts of polyoxyethylene ether monomers and 30 to 50 parts of acrylamide monomers. According to the high-molecular polymer provided by the invention, the N-vinyl pyrrolidone, the polyoxyethylene ether monomer and the acrylamide monomer are subjected to copolymerization modification, so that the room-temperature ionic conductivity of a solid electrolyte prepared from the high-molecular polymer is improved; and the solid electrolyte prepared from the high-molecular polymer has excellent mechanical strength, electrochemical stability and electrochemical window.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high molecular polymers, and particularly relates to a high molecular polymer and a preparation method and application thereof. BACKGROUND

[0002] The solid-state electrolyte has the characteristics of light weight, good viscoelasticity, easy film forming, good thermal stability, and can meet the requirements of ion batteries in many aspects. As one of the commonly used preparation materials of solid-state electrolyte, polyoxyethylene ether is particularly suitable for application scenarios with high requirements on safety, flexibility and low temperature performance due to its good interface stability, convenient processing, intrinsic safety and cost advantage, and is one of the most commercialized solid-state electrolyte systems. However, the polyoxyethylene ether solid-state electrolyte still has the problems of low room temperature conductivity and poor interface contact with some electrodes, which limits its application in high-performance batteries.

[0003] In order to solve the shortcomings of polyoxyethylene ether solid-state electrolyte, researchers try to use methods such as copolymerization, blending, crosslinking, grafting, inorganic fillers, ionic liquids, organic-inorganic hybridization to modify the structure of polyoxyethylene ether to improve its performance, but the room temperature conductivity of polyoxyethylene ether solid-state electrolyte, the mechanical properties and stability of polymer electrolyte still need to be improved.

[0004] CN106356194A discloses a kind of polyacrylamide class solid-state composite polymer electrolyte and preparation method thereof, high molecular weight polyacrylamide containing polar group and good support is used as support phase, polyoxyethylene ether is used as transmission phase, acrylamide and ethylene glycol monomethyl ether acrylate copolymer are used as solubilizer, and an electrolyte material with high lithium ion transference number, high ionic conductivity, small interface resistance and excellent dimensional stability is prepared, but the uniformity and long-term stability of the matrix can not be guaranteed by using physical blending measures in the preparation process of the scheme, and the problem of poor interface contact with the electrode still exists.

[0005] CN102190790A discloses a kind of comb-shaped polymer, electrolyte material and preparation method thereof, by introducing polypropylene oxide with excellent chain flexibility as backbone, increasing the movement of polymer chain segment, introducing polyethylene oxide with different lengths in side chain, preparing comb-shaped polymer macromolecule, improving the conductivity of solid electrolyte, and through radiation crosslinking, the film forming and mechanical properties are good, it is a kind of high molecular solid electrolyte material with positive practical value, but the preparation process of the scheme is complex, the yield is low, and unstable impurities such as halogen are easily introduced, which limits the application development, and the room temperature conductivity still needs to be improved.

[0006] Therefore, how to effectively improve the low room temperature conductivity of polyoxyethylene ether solid-state electrolyte, the poor interface contact with some electrodes and the excellent mechanical properties have become the problems to be solved at present. SUMMARY

[0007] To solve the above technical problems, the application provides a high molecular polymer and a preparation method and application thereof, which utilizes copolymerization modification of N-vinyl pyrrolidone, polyoxyethylene ether monomer and acrylamide monomer to improve the room temperature ionic conductivity of a solid-state electrolyte prepared from the high molecular polymer, and the solid-state electrolyte prepared from the high molecular polymer has excellent mechanical strength, electrochemical stability and electrochemical window.

[0008] To achieve the above purpose, the application adopts the following technical solutions:

[0009] In a first aspect, the application provides a high molecular polymer, and the preparation raw materials of the high molecular polymer include the following components in terms of weight parts:

[0010]

[0011] For example, 20-35 parts can be 20 parts, 22 parts, 24 parts, 25 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts or 35 parts, etc.; for example, 20-40 parts can be 20 parts, 22 parts, 24 parts, 25 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 35 parts, 36 parts, 38 parts or 40 parts, etc.; for example, 30-50 parts can be 30 parts, 32 parts, 34 parts, 35 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts or 50 parts, etc.

[0012] The high molecular polymer provided by the application is copolymerized by N-vinyl pyrrolidone, polyoxyethylene ether monomer and acrylamide monomer, the high molecular polymer containing polyoxyethylene ether fragments has good film-forming property, the solid-state electrolyte containing the high molecular polymer can form a stable interface on the electrode surface, which helps to improve the cycle stability of the battery, and the lone pair electrons carried by the side chain epoxy group have good lithium salt dissociation capacity, which helps to improve the ionic conductivity of the solid-state electrolyte and promote the rapid transmission of lithium ions in the solid-state electrolyte, thereby improving the charging and discharging speed and overall performance of the battery. The N-vinyl pyrrolidone fragments have strong dipole moment complexing properties, which can further improve the ion mobility of the high molecular polymer, and the five-membered ring structure makes the high molecular polymer have excellent thermal stability, so that the solid-state electrolyte prepared from the high molecular polymer has excellent electrochemical stability and mechanical properties. The temperature-sensitive phase separation property of the acrylamide fragments obtains the flexible interface property of amphiphilicity, which can improve the interface contact area of the solid-state electrolyte prepared from the high molecular polymer and the electrode, reduce the interface resistance, and inhibit the crystallization of the polyoxyethylene ether monomer, thereby improving the ionic conductivity.

[0013] The following is a preferred technical solution of the present application, but is not a limitation on the technical solutions provided by the present application. Through the following preferred technical solution, the purpose and beneficial effects of the present application can be better achieved and implemented.

[0014] Preferably, the polyoxyethylene ether monomer comprises a first polyoxyethylene ether monomer and a second polyoxyethylene ether monomer.

[0015] Preferably, the number average molecular weight of the first polyoxyethylene ether monomer is 350-800, for example, it can be 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 510, 520, 530, 540, 550, 560, 570, 580, 590, 600, 610, 620, 630, 640, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, 750, 760, 770, 780, 790 or 800, etc.

[0016] Preferably, the number average molecular weight of the first polyoxyethylene ether monomer is 2000-5000, for example, it can be 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400, 3500, 3600, 3700, 3800, 3900, 4000, 4100, 4200, 4300, 4400, 4500, 4600, 4700, 4800, 4900 or 5000, etc.

[0017] The preferred technical solution of the present application is a high molecular polymer containing a comb-branched structure prepared by compounding a first polyoxyethylene ether monomer with a small molecular weight and a second polyoxyethylene ether monomer with a large molecular weight. The first polyoxyethylene ether monomer constitutes a short-chain polyoxyethylene ether structure, which has excellent segment flexibility and good electrical conductivity performance at room temperature. The second polyoxyethylene ether monomer constitutes a long-chain polyoxyethylene ether structure. The long and short polyoxyethylene ether chains are combined, and the design of the comb-branched structure reduces the crystallinity of polyoxyethylene ether and destroys the regularity of the high molecular polymer chain, so that the high molecular polymer has a low Tg characteristic, and the ion migration efficiency of the solid-state electrolyte containing the high molecular polymer is improved.

[0018] Preferably, the mass ratio of the first polyoxyethylene ether monomer to the second polyoxyethylene ether monomer is 1:(2-6).

[0019] The mass ratio of the first polyoxyalkylene ether monomer to the second polyoxyalkylene ether monomer is 1: (2-6), for example, it can be 1:2, 1:3, 1:4, 1:5 or 1:6. If the first polyoxyalkylene ether monomer with a small molecular weight is too much, the tensile strength of the solid-state electrolyte containing the high polymer will decrease. If the first polyoxyalkylene ether monomer with a small molecular weight is too little, the Tg value of the high polymer will be too high, which will affect the ion migration rate, resulting in a decrease in the ionic conductivity of the solid-state electrolyte containing the high polymer.

[0020] Preferably, the polyoxyalkylene ether monomer includes any one or a combination of at least two of a methyl allyl polyoxyalkylene ether, a polyethylene glycol monoallyl ether or an allyl polyoxyalkylene ether.

[0021] Preferably, the acrylamide monomer includes any one or a combination of at least two of N, N-diethyl acrylamide, N-isopropyl acrylamide, N-acryloylpiperidine, N-n-propyl methacrylamide, N-isopropyl acrylmethylamide, N-cyclopropyl acrylamide, N-acryloylpyrrolidine, N, N-ethyl methacrylamide, N-cyclopropyl methacrylamide or N-ethyl acrylamide.

[0022] Preferably, the preparation raw material of the high polymer further includes a crosslinking agent and an initiator.

[0023] Preferably, the preparation raw material of the high polymer includes 0.2-0.5 parts of the crosslinking agent by weight, for example, it can be 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts, etc.

[0024] Preferably, the preparation raw material of the high polymer includes 0.05-0.2 parts of the initiator by weight, for example, it can be 0.05 parts, 0.1 parts, 0.15 parts or 0.2 parts, etc.

[0025] Preferably, the crosslinking agent includes any one or a combination of at least two of divinyl benzene, N, N-methylene bisacrylamide or a silane coupling agent.

[0026] Preferably, the initiator includes an organic peroxide initiator.

[0027] Preferably, the organic peroxide initiator includes any one or a combination of at least two of t-butyl peroxypivalate, t-butyl peroxybenzoate or t-butyl peroxyethylhexanoate.

[0028] In a second aspect, the present application provides a preparation method of the high polymer as described in the first aspect, and the preparation method of the high polymer includes the following steps:

[0029] Mix raw materials of the high molecular polymer according to the proportion of weight parts, carry out reaction, and obtain the high molecular polymer.

[0030] Preferably, the temperature of the reaction is 60-90℃, for example, it can be 60℃, 65℃, 70℃, 75℃, 80℃, 85℃ or 90℃, etc., and the time of the reaction is 4-6h, for example, it can be 4h, 4.5h, 5h, 5.5h or 6h, etc.

[0031] Preferably, the reaction is carried out under an inert gas atmosphere.

[0032] Preferably, the inert gas comprises nitrogen.

[0033] In a third aspect, the present application provides a high molecular polymer as described in the first aspect for use in a solid-state electrolyte.

[0034] The solid-state electrolyte comprises the high molecular polymer provided in the first aspect 50-80%, lithium salt 10-45%, and inorganic powder filler 0.5-5%.

[0035] Preferably, the lithium salt comprises lithium bistrifluoromethanesulfonimide and / or lithium perchlorate, and preferably is lithium bistrifluoromethanesulfonimide.

[0036] Preferably, the inorganic powder filler comprises any one or a combination of at least two of Al2O3, SiO2 or LLZO.

[0037] The solid-state electrolyte is prepared by a solution casting method or a hot-pressing method.

[0038] Compared with the prior art, the present application has at least the following beneficial effects:

[0039] (1) The high molecular polymer provided by the present application is modified by copolymerization of N-vinylpyrrolidone, polyoxyethylene ether monomer and acrylamide monomer, which improves the room temperature ionic conductivity of the solid-state electrolyte prepared from the high molecular polymer, and the solid-state electrolyte prepared from the high molecular polymer also has excellent mechanical strength, electrochemical stability and electrochemical window.

[0040] (2) The preferred technical solution of the present application further prepares a high molecular polymer containing a comb-type branched structure by compounding a first polyoxyethylene ether monomer with a small molecular weight and a second polyoxyethylene ether monomer with a large molecular weight. The design of the comb-type branched structure reduces the crystallinity of polyoxyethylene ether and destroys the regularity of the high molecular polymer chain, so that the high molecular polymer has a low Tg characteristic, and the ion migration efficiency of the solid-state electrolyte containing the high molecular polymer is improved.

[0041] (3) The room temperature ionic conductivity of the solid-state electrolyte containing the high molecular polymer provided by the present application can reach 1.65×10-4 -5.45 x 10 -4 S / cm, the first coulombic efficiency can reach 94.1-99.7% at 0.5C, the capacity retention rate can reach 95.3-99.3% after 500 cycles, the electrochemical window is greater than or equal to 3.8V, the tensile strength can reach 1.1-3.8Mpa, and the elongation at break can reach 670-2830%. DETAILED DESCRIPTION

[0042] In order to facilitate the understanding of the present application, the present application lists examples and applications, for example, as follows. It should be understood by those skilled in the art that the examples and applications are only to help understand the present application, and should not be regarded as a specific limitation on the present application.

[0043] In the following specific embodiments of the present application, the specific information of the materials used is as follows:

[0044] Allyl polyoxyethylene ether, APEG-800, purchased from Haian Petrochemical;

[0045] Allyl polyoxyethylene ether, APEG-3000, purchased from Haian Petrochemical;

[0046] Methyl allyl polyoxyethylene ether, HPEG-800, purchased from Haian Petrochemical;

[0047] Methyl allyl polyoxyethylene ether, HPEG-2500, purchased from Haian Petrochemical;

[0048] Iso-pentenyl polyoxyethylene ether, TPEG-400, purchased from Haian Petrochemical;

[0049] Iso-pentenyl polyoxyethylene ether, TPEG-2400, purchased from Haian Petrochemical;

[0050] Ethylene glycol monovinyl ether, EPEG-500, purchased from Haian Petrochemical;

[0051] Ethylene glycol monovinyl ether, EPEG-5000, purchased from Haian Petrochemical.

[0052] Examples 1-9

[0053] Examples 1-9 respectively provide a high molecular polymer and a preparation method thereof, and the preparation raw materials of the high molecular polymer are shown in Table 1 (the amount of each preparation raw material of the high molecular polymer in Table 1 is weight fraction), wherein “--” represents that the raw material is not added, and the preparation method is:

[0054] The N-vinyl pyrrolidone, polyoxyethylene ether monomer (including the first polyoxyethylene ether monomer and / or the second polyoxyethylene ether monomer), acrylamide monomer, crosslinking agent and initiator are mixed in a ratio of parts by weight, and are reacted at a temperature of 75℃ for 5h to obtain the high molecular polymer.

[0055] Table 1

[0056]

[0057]

[0058] Example 10

[0059] The present embodiment provides a high molecular polymer and a preparation method thereof.

[0060] The difference from Example 1 is that in the present embodiment, TPEG-400 is replaced by TPEG-300 in equal amount, which is purchased from Haian Petrochemical.

[0061] Example 11

[0062] The present embodiment provides a high molecular polymer and a preparation method thereof.

[0063] The difference from Example 1 is that in the present embodiment, TPEG-400 is replaced by TPEG-1200 in equal amount, which is purchased from Haian Petrochemical.

[0064] Example 12

[0065] The present embodiment provides a high molecular polymer and a preparation method thereof.

[0066] The difference from Example 1 is that in the present embodiment, TPEG-2400 is replaced by TPEG-1000 in equal amount, which is purchased from Haian Petrochemical.

[0067] Example 13

[0068] The present embodiment provides a high molecular polymer and a preparation method thereof.

[0069] The difference from Example 1 is that in the present embodiment, TPEG-2400 is replaced by TPEG-6000 in equal amount, which is purchased from Haian Petrochemical.

[0070] Comparative Example 1

[0071] The present comparative example provides a high molecular polymer and a preparation method thereof.

[0072] The difference from Example 1 is that, in the present example, the raw material for preparing the high molecular polymer does not contain N-vinylpyrrolidone, the addition amount of TPEG-400 is 14 parts, the addition amount of TPEG-2400 is 29 parts, and the addition amount of N,N-diethylacrylamide is 57 parts.

[0073] Comparative Example 2

[0074] The present comparative example provides a high molecular polymer and a preparation method thereof.

[0075] The difference from Example 1 is that, in the present example, the raw material for preparing the high molecular polymer does not contain N,N-diethylacrylamide, the addition amount of N-vinylpyrrolidone is 50 parts, the addition amount of TPEG-400 is 17 parts, and the addition amount of TPEG-2400 is 33 parts.

[0076] Application Examples 1-13 and Comparative Application Examples 1-2

[0077] Application Examples 1-13 and Comparative Application Examples 1-2 respectively provide a solid-state electrolyte and a preparation method thereof.

[0078] The solid-state electrolyte comprises, in terms of mass percentage, the high molecular polymer provided in Examples 1-13 and Comparative Examples 1-2 (65%), LiTFSI (33%), and Al2O3 (2%).

[0079] The solid-state electrolyte is prepared by a solution casting method, specifically:

[0080] The high molecular polymer, LiTFSI, and Al2O3 are mixed and dissolved in dimethylacetamide to form a uniform slurry, which is then cast or coated on a mold to form the solid-state electrolyte by solvent evaporation.

[0081] Test method

[0082] The solid-state electrolytes provided in the above Application Examples 1-13 and Comparative Application Examples 1-2 are subjected to the following performance tests:

[0083] (1) Ionic conductivity (S / cm, 25℃): The solid-state electrolyte is placed in an argon glove box for punching, and a mold cell is used for ionic conductivity testing. The test conditions are: diameter 10 mm, test pressure 200 MPa, and the test is performed using an impedance analyzer (model Bio-logic MTZ-35) at a frequency of 35 MHz to 0.1 Hz.

[0084] (2) Coulombic efficiency (%,30℃): The above battery is subjected to charge-discharge cycle testing, with a voltage range of 2.0-3.8 V and a test rate of 0.5C.

[0085] (3) Electrochemical window (V): at 25℃, the battery was tested, and the cyclic voltammetry scanning voltage was first scanned from the open circuit voltage to -0.5V, and then scanned from -0.5V to 10V, and the scanning speed was 0.5mV / s, and the starting oxidation current position of the battery was confirmed.

[0086] (4) Tensile strength (Mpa): the tensile strength of the solid electrolyte was tested by using a battery separator tensile strength tester (Labthink Lan light, model XLW tensile tester).

[0087] (5) Elongation at break (%) : the solid electrolyte was tested according to GB 13022-91.

[0088] Test results

[0089] The solid electrolytes provided by application examples 1-13 and comparative application examples 1-2 were tested, and the test results are shown in Table 2 below:

[0090] Table 2

[0091]

[0092]

[0093] From the test results, it can be seen that:

[0094] (1) From examples 1 to 13, it can be seen that the solid electrolyte containing the high molecular polymer provided by the application has high room temperature ionic conductivity and excellent mechanical strength, electrochemical stability and electrochemical window, and the room temperature ionic conductivity can reach 1.65×10 -4 -5.45×10 -4 S / cm, the first coulomb efficiency at 0.5C can reach 94.1-99.7%, the capacity retention rate after 500 cycles can reach 95.3-99.3%, the electrochemical window is greater than or equal to 3.8V, the tensile strength can reach 1.1-3.8Mpa, and the elongation at break can reach 670-2830%

[0095] (2) From examples 1 and 6-7, it can be seen that the high molecular polymer containing a comb type branched structure prepared by further limiting the polyoxyethylene ether monomer to include a small molecular weight first polyoxyethylene ether monomer and a large molecular weight second polyoxyethylene ether monomer can achieve better ionic conductivity, promote the rapid transmission of lithium ions in the solid electrolyte, and thus improve the charging and discharging speed and overall performance of the battery.

[0096] (3) As can be seen from Example 1 and Examples 8-9, by further limiting the mass ratio of the first polyoxyethylene ether monomer and the second polyoxyethylene ether monomer, if the first polyoxyethylene ether monomer with a small molecular weight is too much, the strength of the solid-state electrolyte containing the high molecular polymer decreases, and if the first polyoxyethylene ether monomer with a small molecular weight is too little, the Tg value of the high molecular polymer is too high, affecting the ion migration rate, and the ionic conductivity of the solid-state electrolyte decreases.

[0097] (4) As can be seen from Example 1 and Comparative Examples 1-2, the high molecular polymer provided by the present application copolymerizes N-vinyl pyrrolidone, a polyoxyethylene ether monomer, and an acrylamide monomer, so that the solid-state electrolyte has excellent mechanical strength, electrochemical stability, and electrochemical window.

[0098] The applicant declares that the above is only a specific embodiment of the present application, but the protection scope of the present application is not limited thereto. It should be understood by those skilled in the art that any changes or replacements within the technical scope disclosed by the present application can be easily thought of by any person skilled in the art, and all fall within the protection scope and disclosure scope of the present application.

Claims

1. A high molecular polymer, characterized by, The raw material for preparing the high molecular polymer comprises the following components in parts by weight: N-vinyl pyrrolidone 20-35 parts; Polyoxyethylene ether monomer 20-40 parts; Acrylamide monomer 30-50 parts.

2. The high molecular polymer of claim 1, wherein, The polyoxyethylene ether monomer comprises a first polyoxyethylene ether monomer and a second polyoxyethylene ether monomer; Preferably, the number average molecular weight of the first polyoxyethylene ether monomer is 350-800; Preferably, the number average molecular weight of the first polyoxyethylene ether monomer is 2000-5000.

3. The high molecular polymer of claim 2, wherein, The mass ratio of the first polyoxyethylene ether monomer to the second polyoxyethylene ether monomer is 1:(2-6).

4. The macromolecular polymer according to any one of claims 1 to 3, characterized in that, The polyoxyethylene ether monomer comprises any one or a combination of at least two of a methylenallyl polyoxyethylene ether, a polyethylene glycol monoallyl ether or an allyl polyoxyethylene ether.

5. The macromolecular polymer of any one of claims 1-4, wherein, The acrylamide monomer comprises any one or a combination of at least two of N,N-diethyl acrylamide, N-isopropyl acrylamide, N-acryloyl piperidine, N-n-propyl methacrylamide, N-isopropyl acrylamide, N-cyclopropyl acrylamide, N-acryloyl pyrrolidine, N,N-ethyl methacrylamide, N-cyclopropyl methacrylamide or N-ethyl acrylamide.

6. The macromolecular polymer of any one of claims 1-5, wherein, The raw material for preparing the high molecular polymer further comprises a crosslinking agent and an initiator.

7. The polymer of claim 6, wherein The raw material for preparing the high molecular polymer comprises the crosslinking agent in 0.2-0.5 parts by weight; Preferably, the raw material for preparing the high molecular polymer comprises the initiator in 0.05-0.2 parts by weight; Preferably, the crosslinking agent comprises any one or a combination of at least two of divinyl benzene, N,N-methylene bisacrylamide or a silane coupling agent; Preferably, the initiator comprises an organic peroxide initiator; Preferably, the organic peroxide initiator comprises any one or a combination of at least two of t-butyl peroxypivalate, t-butyl peroxybenzoate or t-butyl peroxyethylhexanoate.

8. A method of producing a high molecular polymer as claimed in any one of claims 1 to 7, characterized in that, The method for preparing the high molecular polymer comprises the following steps: Mixing the raw material for preparing the high molecular polymer according to the proportion in parts by weight, and reacting to obtain the high molecular polymer.

9. The method for preparing the polymer according to claim 8, characterized in that, The reaction temperature is 60-90°C, and the reaction time is 4-6h; Preferably, the reaction is carried out in an inert gas atmosphere; Preferably, the inert gas comprises nitrogen.

10. Use of the high molecular polymer according to any one of claims 1-7 in a solid-state electrolyte.

Citation Information

Patent Citations

  • Comb-like polymer, electrolyte material and method for preparing same

    CN102190790A

  • Polyacrylamide (PAM) solid compound polymer electrolyte and preparation method thereof

    CN106356194A

  • Water-soluble polymer, production method thereof, and application thereof

    CN101171273A

  • Optical adhesive and preparation method thereof

    CN117004327A

  • High-compaction dispersion material, preparation method thereof and high-compaction flexible positive pole piece

    CN120209225A